2011
DOI: 10.1177/1545109711399657
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in HIV-Infected Women on Antiretroviral Therapy Living in the Tropics

Abstract: The effects of HIV/AIDS and antiretroviral drugs on vitamin D metabolism are still mostly unknown. This was a cross-sectional study to estimate the prevalence of vitamin D deficiency and identify its association with the clinical and metabolic parameters among 214 HIV-positive female patients on antiretroviral therapy (ART) in Brazil. The prevalence of vitamin D deficiency (< 30 ng/ml) was 40.65% (87/214). Hypercholesterolemia, high LDL-c, duration of use of current antiretroviral regimen, hypertriglyceridemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 41 publications
2
19
1
Order By: Relevance
“…Vitamin D deficiency has been reported to be higher in various age groups of HIVinfected individuals, ranging from 60% of adolescents and young adults with serum 25(OH)D levels of less than 10 ng/mL in the Netherlands (32) (40° N) to more than 80% of adults, with a mean age of 41 years, showing serum 25(OH)D levels of less than 18 ng/ mL in Italy (30° N). In a group of premenopausal HIV women with a mean age of 40 years living in the city of Recife (10° S), 60% of them with lipodystrophy, 80% with dyslipidemia and 38% with metabolic syndrome, we found a 41% prevalence of vitamin D deficiency using a cut point of 30 ng/mL for serum 25(OH)D. After full adjustments, total serum cholesterol levels and the duration of ART were independently associated with vitamin D deficiency (33).…”
Section: Vitamin D and Insulin Resistancementioning
confidence: 84%
“…Vitamin D deficiency has been reported to be higher in various age groups of HIVinfected individuals, ranging from 60% of adolescents and young adults with serum 25(OH)D levels of less than 10 ng/mL in the Netherlands (32) (40° N) to more than 80% of adults, with a mean age of 41 years, showing serum 25(OH)D levels of less than 18 ng/ mL in Italy (30° N). In a group of premenopausal HIV women with a mean age of 40 years living in the city of Recife (10° S), 60% of them with lipodystrophy, 80% with dyslipidemia and 38% with metabolic syndrome, we found a 41% prevalence of vitamin D deficiency using a cut point of 30 ng/mL for serum 25(OH)D. After full adjustments, total serum cholesterol levels and the duration of ART were independently associated with vitamin D deficiency (33).…”
Section: Vitamin D and Insulin Resistancementioning
confidence: 84%
“…The two articles that reported the lowest frequency of vitamin D deficiency or insufficiency were undertaken in Brazil and Tanzania. 8,41 Considering the countries where the other trials were performed, no clear trend in the prevalence of hypovitaminosis D was found, with studies performed in similar populations within the same country (eg, France, Italy) reporting quite different results. 10,28,32,50 We observed similar inconsistencies while exploring the overall frequencies of hypovitaminosis D taking into account the use of vitamin D supplements.…”
Section: Vitamin D Deficiencymentioning
confidence: 89%
“…27,31,41 Considering other HIV-related risk factors, patchy correlations were found between HIV viral load, duration of ART, duration of HIV, plasma neopterin, or soluble tumor necrosis factor-alpha receptor I and vitamin D deficiency. 6,8,9,23,25,28,37,52,54,57 Adverse health outcomes related to vitamin D deficiency in HIV-infected patients Very few studies investigated the detrimental effects of vitamin D deficiency on health outcomes other than bone diseases in HIV+. They were primarily cross-sectional correlation analyses, and it was therefore not possible to establish a cause-effect relationship.…”
Section: Vitamin D Deficiencymentioning
confidence: 99%
See 2 more Smart Citations